HARMONIZING THE TAPESTRY OF BREAST LESIONS IN WOMEN: AN INTEGRATED EXPLORATION OF CLINICAL, RADIOLOGICAL, CYTOLOGICAL, HISTOPATHOLOGICAL, AND IMMUNOHISTOCHEMICAL PATTERNS - SANGEETHA NAGALINGAM; BALAJI VENKATARAMAN; SWETHA MURALIDHARAN (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The study aimed to evaluate and compare the diagnostic validity of clinical examination, radiological imaging, Breast Imaging Reporting and Data System (BIRADS), and cytological examination in women presenting with breast lumps, using histopathology as the gold standard. Methods: A cross-sectional study was conducted among 96 women with palpable breast lumps at a tertiary teaching hospital over a 2-year period. Each patient underwent clinical examination, mammography (BIRADS scoring), and fine-needle aspiration cytology. The triple test scores were analyzed for diagnostic concordance, and histopathological examination was performed in all cases. Statistical analysis included sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and 95% confidence intervals (CIs). Results: Among 96 participants, 61 (63.5%) had benign and 35 (36.5%) had malignant lesions confirmed histopathologically. Clinical diagnosis showed the highest sensitivity (93.5%; 95% CI: 78.6–98.2), cytology showed perfect specificity (100%; 95% CI: 94.1–100), and radiology demonstrated moderate sensitivity (77.4%; 95% CI: 59.2–88.7) and specificity (96.9%; 95% CI: 88.2–99.5). The triple test achieved an overall concordance rate of 83.3%. PPV and NPV for clinical, radiological, and cytological evaluations were 93.5%, 77.4%, 100%, and 96.9%, 96.9%, 100%, respectively. Conclusion: The triple assessment method provides a highly accurate, non-invasive, and cost-effective diagnostic approach for breast lumps. Clinical examination and cytology together offer optimal diagnostic reliability. Integrating histopathology and immunohistochemistry enhances diagnostic precision and guides treatment, particularly in resource-limited settings.